ผลของซิลิกอนจากอุตสาหกรรมซีเมนต์ต่อการเจริญเติบโต ผลผลิต และการเคลื่อนย้ายซิลิกอนของถั่วลิสงพันธุ์ขอนแก่น 84-8 - งามล้วน ศรัณภิรมย์; ชคตระการ สมชาย; ชุติมานุกูล พฤกษ์ (Thai Journal of Science and Technology, 2019)
Abstract Peanut is one of the economically important legumes, which are rich sources of protein and carbohydrate, with wide spread growing area throughout Thailand. However, the use of silicon, as a by-product from cement industry, is considered to be various benefits for the agricultural sector. The aim of this study was to investigate the effect of silicon levels from the cement industry on the growth and yield of peanut. The experiment was arranged in completely randomized design (CRD) with 10 replications consisting of 5 levels of silicon; 0, 50, 100, 150 and 200 kg per rai. The results showed that silicon gave the effects on plant height and branch number per plant, but all silicon levels had no significant difference on dry matter, yield, yield components and silicon translocation in plant parts. Therefore, the growth and the yield of peanut (A. hypogaea var. Khon Kaen 84-8) did not increase by using different silicon levels when compared with those by non-silicon. Keywords: cement industry; growth; peanut; silicon; translocation; yield